Induction and modulation of inflammatory networks by bacterial protein toxins - Backert, Steffen; König, Wolfgang; König, Brigitte; Arnold, Ralf (The Comprehensive Sourcebook of Bacterial Protein Toxins, 2006)
An understanding of infectious pathobiology also needs to consider the combined action of bacterial toxins in conjunction with the whole microorganism, as well as its soluble exoproducts in a complete system. This may result in altered cellular responses compared to the individual toxin on its own. This chapter focuses on individual pathogenicitiy factors, but also on defined and up to now unresolved disease processes. The complexity of host defense have been described with emphasis on the mucosal system, as well as inflammatory cells and mediators. Today, sophisticated biochemical and genetic tools are being used to elucidate the molecular details surrounding host-pathogen interactions. These studies continue to provide detailed information on basic cellular mechanisms and offer novel avenues of potential chemotherapeutic intervention and even the possibility of introducing beneficial agents into eukaryotic cells. However, bacterial proteins including toxins can enter the cells, they can integrate themselves, and sometimes they abuse eukaryotic signaling mechanisms or deviate the immune response by their mimicry. Although a wide range of microbe-host relation ships can ultimately lead to disease, the two most general strategies used by pathogenic microbes may be described in military terms as "frontal" and "stealth" assaults. © 2006 Elsevier Inc. All rights reserved.
Created from Fastlane, Scopus look-up